Tirando del hilo desde el Gran Chaco: significación y alcance del estudio de las figuras de hilo tradicionales - José Braunstein (Journal de la Société des Américanistes)
This paper is a is a reflection on the studies of string figures. The main aim of the article is to exhibit the general aspects of the handicraft, its meaning for culture and the scope of its study for anthropological sciences. On the basis of the author’s ethnographic experience of more than half a century in the South American Gran Chaco, it shows the development of a line of research that, from Marcel Mauss’ definition of “body techniques,” proposes a method to advance in the phylogenetic understanding of human societies.